A monograph of the Afrotropical Cassidinae (Coleoptera: Chrysomelidae). Part 6. Revision of the tribe Cassidini 3, the genus Cassida L. - Borowiec, Lech; Świętojańska, Jolanta (Zootaxa, 2022)
The genus Cassida Linnaeus, 1758 is revised and 103 species are recognized as valid, all distributed in Sub-Saharan Africa and the south-western part of the Arabian Peninsula. Twenty-four species are described as new: Cassida bamendana sp. nov. (Cameroon), Cassida benaadirensis sp. nov. (Ethiopia and Somalia), Cassida elgonensis sp. nov. (Kenya), Cassida emontinensis sp. nov. (South Africa), Cassida garambana sp. nov. (Democratic Republic of Congo), Cassida heroni sp. nov. (Mozambique and South Africa), Cassida kantnerorum sp. nov. (Malawi), Cassida leleupi sp. nov. (Democratic Republic of Congo and Rwanda), Cassida minutissima sp. nov. (Somalia), Cassida nigeriana sp. nov. (Nigeria), Cassida oromiaensis sp. nov. (Ethiopia), Cassida overlaeti sp. nov. (Democratic Republic of Congo), Cassida oxylepiformis sp. nov. (South Africa), Cassida rabaiensis sp. nov. (Kenya), Cassida rogozinskii sp. nov. (Cameroon), Cassida satanas sp. nov. (Uganda), Cassida senegalensis sp. nov. (Senegal), Cassida shimba sp. nov. (Kenya, Tanzania, Mozambique and South Africa), Cassida sparteiformis sp. nov. (Angola), Cassida stipidosa sp. nov. (Ethiopia), Cassida villersi sp. nov. (Burkina Faso and Niger), Cassida voiensis sp. nov. (Kenya), Cassida wanati sp. nov. (South Africa), and Cassida wittmeri sp. nov. (South Africa). The following new synonyms are proposed: Cassida callosicollis Spaeth, 1926 = Cassida magilensis Spaeth, 1926 syn. nov.; Cassida eluta Boheman, 1862 = Cassida cherenica Spaeth, 1917 syn. nov.; Cassida lacrymosa Boheman, 1854 = Cassida trepidula Spaeth, 1932 syn. nov.; Cassida praetimida Spaeth, 1912 = Cassida chapuisi Spaeth, 1912 syn. nov.; Cassida troglodytes Boheman, 1834 = Cassida impompalis Spaeth, 1924 syn. nov. = Cassida lueboensis Spaeth, 1932 syn. nov. Cassida setosa Chapuis, 1880 is a valid species and removed from synonymy with Cassida innotata Boheman, 1854. Colour photos, including intraspecific variablity, a key to species and maps of distribution are given.